Pengaruh Terapi Musik Klasik Beethoven untuk Mengurangi Kecemasan pada Ibu Bersalin Pre Operasi Sectio Caesar - Keumalahayati Keumalahayati; Supriyanti Supriyanti (Jurnal Keperawatan, 2018)
Anxiety in preoperative patients with Sectio Caesarea is a specific anxiety, namely concern about operating procedures, anesthesia procedures, information deficits, and concerns about family financial problems, concerns about themselves and the baby to be born. Music is applied into therapy, because music can restore, and maintain physical, mental, emotional, social and spiritual health. The provision of classical music therapy can releases pain and reduces stress levels, so that it can cause a decrease in anxiety. The purpose of this study was to determine the effect of Beethoven classical music therapy to reduce anxiety in cesarean section. This study used a pre-experimental design with the design of two group control interventions. The number of samples in this study were 10 people each in the intervention and control groups. Sampling is done using accidental techniques. Data analysis using the t-dependent test. The t-dependent statistical test results can be concluded that there is a significant influence of classical music therapy to reduce anxiety in cesarean section delivery mothers in the intervention and control groups (P = 0.041). From the results of this study it is known that Beethoven classical music therapy is effective for reducing anxiety, so that nurses can apply classical music therapy in providing care to cesarean section mothers.